2021
DOI: 10.1002/zamm.202100167
|View full text |Cite
|
Sign up to set email alerts
|

A study on nanoliquid flow with irregular heat source and realistic boundary conditions: A modified Buongiorno model for biomedical applications

Abstract: Titanium dioxide plays a vital role in cancer therapy methods (including photothermal therapy and photodynamic therapy), skincare products, heat exchangers, and car radiators. Therefore, the dynamics of the TiO 2 nanomaterial with H 2 O as basefluid over a nonlinearly stretched surface is investigated. For realistic nanoliquid modeling, the conventional Buongiorno model has been improvised (called modified Buongiorno model [MBM]) by incorporating the effective thermophysical properties of the nanoliquid. Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The highly non-linear ordinary differential equations (ODEs), Equations ( 6)-( 8), along with the boundary condition, Equation ( 9), are solved by BVP5C using the MATLAB software (see [42] for more details). To accomplish this, assume…”
Section: Numerical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The highly non-linear ordinary differential equations (ODEs), Equations ( 6)-( 8), along with the boundary condition, Equation ( 9), are solved by BVP5C using the MATLAB software (see [42] for more details). To accomplish this, assume…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…The highly non‐linear ordinary differential equations (ODEs), Equations ()–(), along with the boundary condition, Equation (), are solved by BVP5C using the MATLAB software (see [42] for more details). To accomplish this, assume f=S1fβ€²=S2fβ€²β€²badbreak=S3fβ€²β€²β€²=S3β€²ΞΈ=S4ΞΈβ€²=S5ΞΈβ€²β€²=S5β€²Ο•badbreak=S6Ο•β€²=S7Ο•β€²β€²=S7β€²$$\begin{equation} \def\eqcellsep{&}\begin{array}{@{}*{5}{c}@{}} { \def\eqcellsep{&}\begin{array}{*{20}{c}} { \def\eqcellsep{&}\begin{array}{*{20}{c}} {f\ = {S}_1\ }&{\ f^{\prime} = {S}_2\ } \end{array} }&{\ f^{\prime\prime} = {S}_3\ }&{ \def\eqcellsep{&}\begin{array}{*{20}{c}} {\ f^{\prime\prime\prime} = S_3^{\prime}\ }&{\theta \ = {S}_4\ } \end{array} } \end{array} }\\[6pt] { \def\eqcellsep{&}\begin{array}{*{20}{c}} { \def\eqcellsep{&}\begin{array}{*{20}{c}} {\ \theta ^{\prime} = {S}_5\ }&{\ \theta ^{\prime\prime} = S_5^{\prime}\ } \end{array} }&{\phi \ = {S}_6\ }&{ \def\eqcellsep{&}\begin{array}{*{20}{c}} {\ \phi ^{\prime} = {S}_7\ }&{\ \phi ^{\prime\prime} = S_7^{\prime}} \end{array} } \end{array} } \end{array} \end{equation}$$…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…Arrekara et al. [23] looked at a simulation of nanoliquid flow with an erratic heat source and realistic boundary conditions, where the rate of heat transfer is maximised using RSM. Rana and Gupta [24] discovered Von KΓ‘rmΓ‘n's swirling flow of nanoliquid throughout a revolving disc with Stefan blowing and many slip effects using the nonlinear Boussinesq Approximation Sensitivity computation.…”
Section: Introductionmentioning
confidence: 99%
“…Puneet and Gupta et al [22] used Response Surface Technique to optimise the FEM approach to the nonlinear convective and radiative flow of hybrid nanofluid across a revolving cone with Hall current. Arrekara et al [23] looked at a simulation of nanoliquid flow with an erratic heat source and realistic boundary conditions, where the rate of heat transfer is maximised using RSM. Rana and Gupta [24] discovered Von KΓ‘rmΓ‘n's swirling flow of nanoliquid throughout a revolving disc with Stefan blowing and many slip effects using the nonlinear Boussinesq Approximation Sensitivity computation.…”
Section: Introductionmentioning
confidence: 99%
“…Akram et al (Akram et al, 2022) analyzed the electroosmotic movement of silver-water HNF controlled by using two altered methods for NF including the MBNM. Areekara et al (Areekara et al, 2022) suggested a study on NF movement with asymmetrical heat foundation and representative boundary conditions with the application by MBNM.…”
Section: Introductionmentioning
confidence: 99%